Asymptotic Dissipativity of Lorenz model with Markov Switching for the City Development - Kinash, A.V.; Khimka, U.T. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2016)
In the work activity of the city system, described by generalized Lorentz model, is considered. It is assumed the existence of external influence on the land rate change in the city that is described by diffusive term and ergodic Markov processes. With the made assumptions, asymptotic dissipativity conditions of the initial system are set. Stationary points of the model of city economical activity are studied based on the results obtained for asymptotic dissipativity of generalized Lorentz model.